Mindfulness dan Kesejahteraan Psikologis pada Remaja - Wenita Cyntia Savitri; Ratih Arruum Listiyandini (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2017)
Abstract: During adolescence, individuals experience various changes physically, psychologically, and socially, which may bring issues that can potentially disrupt adolescents’ psychological well-being. The aim of this study was to analyze the influence of a tendency for being present in the moment, or trait mindfulness, on psychological well-being among adolescents. The sample for this study was 200 adolescents living in Greater Area of Jakarta, collected by incidental sampling. This study used an adapted Child and Adolescent Mindfulness (CAMM) Scale to measure trait mindfulness and an adapted Scale of Psychological Well-being (SPWB) to measure six dimensions of psychological well-being. Data is analyzed by regression analysis. Regression results indicated that trait mindfulness has positive and significant contribution in every dimension of psychological well-being in adolescents, specifically on environmental mastery. The implication of this research will be discussed in the end of the paper.Abstrak: Remaja mengalami perbedaan dan perubahan secara fisik, psikis, maupun sosial sehingga, dapat memunculkan beberapa masalah-masalah yang dapat mengganggu kesejahteraan psikologis. Tujuan penelitian ini adalah untuk menganalisis pengaruh dari kemampuan untuk memberi perhatian penuh, yang disebut sebagai mindfulness, terhadap kesejahteraan psikologis pada remaja. Sampel dalam penelitian ini berjumlah 200 orang remaja di wilayah Jabodetabek, yang dipilih dengan menggunakan teknik incidental sampling. Penelitian menggunakan adaptasi skala Child and Adolescent Mindfulness Measure (CAMM) untuk mengukur mindfulness dan adaptasi skala Scale of Psychological Well-being (SPWB) untuk mengukur keenam dimensi kesejahteraan psikologis. Data dianalisa menggunakan uji regresi. Hasil uji regresi menunjukkan bahwa mindfulness berperan positif dan signifikan terhadap setiap dimensi kesejahteraan psikologis pada remaja, khususnya pada dimensi penguasaan lingkungan. Implikasi dari hasil penelitian akan dijelaskan di bagian akhir.